The Promise of a Multi-Disciplinary, Mixed-Methods Approach to Inform Insect Pest Management: Evidence From Wyoming Alfalfa - Jabbour, Randa; Noy, Shiri (Frontiers in Sustainable Food Systems, 2020)
Pest management strategies involve a complex set of considerations, circumstances, and decision-making. Existing research suggests that farmers are reflexive and reflective in their management choices yet continue to employ curative rather than preventative strategies, and opt for chemical over biological solutions. In this piece, we detail work from a two-year, multidisciplinary, mixed-methods study of insect pest management strategies in alfalfa in Wyoming, integrating data from four focus groups, a statewide survey, and biological sampling of production fields. We outline how these different sources of data together contribute to a more complete understanding of the challenges and strategies employed by farmers, and specifically on biological pest control. We applied this approach across alfalfa hay and seed crop systems. Relatively few farmers acknowledged biological control in focus groups or surveys, yet biological exploration yielded abundant parasitism of common pest alfalfa weevil. On the other hand, parasitism of seed alfalfa pest Lygus was far less common and patchy across fields. It is only in integrating quantitative and qualitative, biological and social data that we are able to generate a more complete portrait of the challenges and opportunities of working with farmers to embrace a preventative paradigm. In doing so, we offer insights on possible barriers to the adoption of preventative insect management strategies and provide a case study of integrating social science and biophysical techniques to better understand opportunities to expand biological pest control in cropping systems.